Ariel Gel: harnessing sustainability for competitive advantage - Bernon, Mike (Henry Stewart Talks, 2018)
This case study describes the development of Ariel Gel, which was designed and marketed to highlight its environmental benefits. Ariel Gel is more concentrated than the company’s older products, its packaging is recyclable, and it works well at low temperatures, making it more environmentally friendly. However, these factors also helped Ariel to reduce costs across its supply-chains.